Blue-Marketing Strategy: The Opportunities and Challenges of Big Data Integration in Coastal MSMEs - Tito Wira Eka Suryawijaya; Muhammad Tata Rizky Setyo Utomo; Peter S. Fader; Febrianur Ibnu Fitroh Sukono Putra; Azna Abrory Wardana; Mochammad Eric Suryakencana Wibowo (Jurnal Telekomunikasi dan Informatika, 2024)
Changing times leading to digitalization have brought about profound changes in a number of industrial sectors, including maritime and fisheries. Micro, small and medium enterprises (MSMEs) in this sector face significant sales challenges, especially amidst post-pandemic market turmoil. This research objective understands how big data systems work in order to increase marketing efficiency in the marine and fisheries business sector. By detailing the digitization process and application of big data in this context, this research will provide a clearer picture of how marine and fisheries MSMEs can utilize technology to improve their marketing performance. This research was conducted using a quantitative approach. Aims to understand the influence of the application of big data on the marketing efficiency of marine and fisheries MSMEs. The research population involved more than 5000 MSME players, with a sample of 210 respondents selected using the purposive sampling method. The main research instrument is a questionnaire. These findings show that the implementation of the Blue-Marketing Strategy in marine and fisheries MSMEs has proven to have a positive impact on sales growth, brand awareness and customer retention, with an emphasis on sustainability as the main factor for increasing marketing effectiveness through empowering consumers in making sustainable choices. The research proposes a new concept regarding responsiveness to market dynamics, especially through implementationBlue-Marketing Strategy, as an innovative approach to dealing with changes in the post-pandemic market. Meanwhile, the integration of Marketing Strategy into the Blue Economy is considered a significant step that not only creates new marketing opportunities but also supports the sustainability of the marine ecosystem and the growth of the Blue Economy sector as a whole.